Life cycle assessment of post-combustion CO2 capture: A comparison between membrane separation and chemical absorption processes. (January 2018) - Giordano, Lorena; Roizard, Denis; Favre, Eric
Highlights: A lifecycle assessment of post-combustion CO2 capture processes is carried out. Lifecycle emissions of membrane separation and chemical absorption were compared. Impacts of membrane systems strongly depend on polymer type and layer thickness. Membrane separation can reduce lifecycle emissions compared to chemical absorption. The greatest reductions occur for human toxicity and impacts on water ecosystems. Abstract: Carbon capture technologies are regarded as promising options to mitigate CO2 emissions from large point sources, such as power generation facilities and energy intensive industries. However, CO2 capture technologies have several environmental impacts, from the system infrastructure production stage to the end of their lifetime, because of the consumption of resources in the form of materials and energy, as well as the formation of chemical by-products. All these aspects should be taken into account in order to assess and compare the real environmental sustainability of the CO2 capture processes. It is well established that life cycle assessment (LCA) represents a powerful tool to evaluate the most significant environmental impacts of CO2 capture technologies throughout their lifetimes. Using LCA methodology, this study aimed to compare life cycle emissions of membrane separation and chemical absorption processes for the post-combustion capture of one tonne of CO2 from a subcritical coal-fired power plant. Environmental impacts were evaluated considering a hybrid approach for the life cycle inventory, combining physical and economic input data. Simulation results highlighted that life cycle emissions of CO2 capture based on membrane separation process were strongly related to membrane material and thickness of the dense active layer, influencing the net power consumption and membrane area requirement. Membrane configurations investigated allowed to reduce to such an extent environmental impacts compared to CO2 capture based on monoethanoalmine (MEA) absorption. The greatest reduction potential was observed for human toxicity and impacts on freshwater and marine ecosystems, because of the elimination of environmental concerns related to solvent manufacturing and disposal of amine reclaimer wastes.